Frequency of preoperative anxiety and associated factors among adult surgical patients undergoing elective surgery in Civil Hospital Karachi - Kazim, Erum; Abdul Muqeet; Munsab, Rabbia; Zafar, Rabia; Taj, Javeria; Fatima, Anoosha (Journal of the Pakistan Medical Association, 2025)
Objectives: To determine the frequency of preoperative anxiety and associated factors among patients undergoing elective surgery. Method: The cross-sectional study was conducted at Civil Hospital Karachi from June 1 to August 1, 2024, and comprised adult patients of either gender who were due to undergo elective surgery. Data was collected through face-to-face interviews using a standardised questionnaire. Anxiety levels and information needs were assessed using the Amsterdam Preoperative Anxiety and Information Scale. Data was analysed using SPSS 22. Results: Of the 390 patients with mean age 39.93±10.73 years (range: 19-50 years), 167(42.8%) were males and 223(57.2%) were females. Overall, mean anxiety level was 14.50±4.36, with 314(80.5%) patients exhibiting high levels of preoperative anxiety compared to 76(19.5%) who reported low anxiety. Age, education level, marital status and the number of previous surgeries were significantly associated with preoperative anxiety (p<0.05), while systemic illnesses did not significantly correlate with anxiety (p>0.05). Conclusions: The level of preoperative anxiety was found to be significantly high among patients undergoing elective surgery. Improved patient education and communication strategies can help alleviate anxiety and enhance surgical outcomes. Key Words: Preoperative anxiety, Elective surgery, Anxiety predictors, Patient education.